Certain determinants for a career in management for selected UPV-CM undergraduate and graduate students - Frondosa, Kristin P.; Hortillas, Florabelle L.; Leada, Rya M.; Rubias, Ma. Carla M. (1997)
A career is a property of both the individual and the social structure. It is individual who possess the occupational information, develops career attitudes, values, and exxperiences, and makes career choices. In this sense, this study aims to find out he determinants why students choose management as their career choice. With this, problems arise, the researchers have to find out what reasons to do the respondnets have for choosing management, whether management is their initial career choice, what factors influenced them and now that they are studying management, what are their attitudes towards their course. The objectives are patterned after these problems. The main reason why this study caught the attention of the researchers is due to the fact that they are interested in pursuing a management career. Aside from this, management is the process of reaching organizational goals by working with and through people and other organizational framework. The researchers are fascinated with the interaction within the organization in achieving desired goals. This study is focused on outlining the importance of management to our society, presenting a definition of management and the management process and explaining the universality of management. There is also the importance of management as a profession or a career. The specific focus are on the reasons why people choose management and the factors which influenced them to choose management as a career. The responses to these questions are measured through interviews and surveys. The respondents of this study are the students studying at the University of the Philippines in the Visayas. The total population of respondents is one hundred sixty-two (162), unevenly distributed into three (3) groups, namely the First Year, the Fourth Year/Graduating nd the Graduate Studies students. From this group, a sample of ninety-seven (97) respondents or sixty percent (60%) is taken using stratified random sampling with proportional allocation. This consists of fifty-two (52) from the First Year, twenty-four (24) from the Fourth Year and twenty-one (21) from the Graduate Studies. The respondents include twenty-six (26) males and seventy-one (71) females. The result of the study shows that among the different reasons for choosing management, Fifty-four (54) out of ninety-seven (97) respondents cited that it is because they feel a sense of fulfillment in studying management than any other course. As for the factors that influenced them, majority answered that it was their personal choice although there were also influences from other persons like guidance counselors or their parents. majority of the respondents, on the other hand, answered that they were satisfied with their choice.
Research Paper (Mgt 200 - Business Research) -- [Iloilo City] : UPV-CM, March, 1997.